Annotated birds dataset for object detection using deep learning, Skagen & Klim - Annotated birds datasets for object detection using deep learning, Skagen and Klim - Alqaysi, Hiba (Mid Sweden University, 2021)
The two datasets are of image frames of birds collected in two sites in Denmark, namely Skagen and Klim. Each image frame has its corresponding text file that contains the coordinates of bounding boxes containing the objects. The datasets are used in the following publication: "A Temporal Boosted YOLO-Based Model for Birds Detection around Wind Farms". The publication should be referenced when using the dataset by other researchers.

The datasets were collected at two sites in Denmark over the course of a few months in 2017 and 2018. They were manually annotated using the freely available LabelImg online tool. The Skagen dataset was collected at the Skagen Grey Lighthouse, Center of Migratory Birds using a pair of wide-angle, monochrome cameras firmly affixed to rigid boxes. The Kilm set was collected at Klim Fjordeholme using the same camera setup; except the cameras were mounted on tripods.

The datasets were collected at two sites in Denmark over the course of a few months in 2017 and 2018. The datasets were manually annotated using the freely available LabelImg online tool. The Skagen dataset was collected at the Skagen Grey Lighthouse, Center of Migratory Birds using a pair of wide-angle, monochrome cameras firmly affixed to rigid boxes. The Kilm data were collected at Klim Fjordeholme using the same camera setup; except, here, the cameras are mounted on tripods.

Datasetet består av bilder på fåglar i vindkraftsparker. Den samlas in i två vindkraftsparker i Danmark, Skagen och Klim. Varje bild har sin motsvarande textfil som innehåller objektets plats. Datasetet ligger till grund för följande publikation: "A Temporal Boosted YOLO-Based Model for Birds Detection around Wind Farms"

Se den engelska katalogsidan för mer information.
Annotated birds dataset for object detection using deep learning, Skagen & Klim - Annotated birds datasets for object detection using deep learning, Skagen och Klim
Keywords: YOLOv4; YOLOv4; sky surveillance; sky surveillance; object detection; object detection; Computer graphics and computer vision; Datorgrafik och datorseende